A Case Report: Benzene Contamination in Shampoo - Elanda Fikri; Yura Witsqa Firmansyah (Fakultas Teknik, 2023)
The availability of safe personal care products is a right that must be obtained by global consumers. There have been several reports of cases of chemical contamination in personal care products, for example, Benzene contamination. Recently on 18 October 2022, the U.S. The Food and Drug Administration withdrew shampoo with several brands because Benzene contamination with concentrations exceeding the established quality standards had been detected. This study aims to disseminate information on shampoo products contaminated with Benzene and how the mitigation is carried out by the Indonesian authorities. This research is descriptive research with a case report study design approach. The data used in this study is in the secondary data obtained from the websites of the United States state authorities (Food and Drug Administration) and the National Agency of Drug and Food Control (BPOM) Indonesia and journals. Data collection was carried out on 18-21 October 2022. From the results of the data search, there were 19 dry shampoo products from the Unilever company that were contaminated with Benzene. Two of these products are notified in Indonesia. Benzene contamination in shampoo is thought to originate from the propellant. The propellant/propellant is the material needed by the product in the form of an aerosol dosage form which functions to push the contents of the product out of the package with a certain pressure. BPOM also continues to monitor this issue nationally and internationally.